Perawatan Tanaman Kelapa Sawit Di Lahan Masyarakat Desa Bukit Cermin Hilir Kecamatan Dolok Masihul Kabupaten Serdang Bedagai - Yazid, Abu; Mahyunis, Mahyunis; Napitu, Patuan L; Simangunsong, Samuel; Nurhamdi, M; Imran, Ali; Nasution, Nafis M (CV. IRA PUBLISHING, 2024)
To increase palm oil production, special attention must be given to various factors that influence plant growth. One crucial step is ensuring optimal care for immature plants to improve their quality and yield. Unfortunately, many smallholder palm oil farmers face limited knowledge and resources to apply proper care practices. Therefore, targeted efforts are needed to help them understand the importance of palm oil plant care to sustain and enhance the profitability of this sector. In Bukit Cermin Hilir Village, Dolok Masihul District, Serdang Bedagai Regency, palm oil plant care uses two main techniques. The first technique is pruning, which involves removing fronds below the fruit bunches. This process facilitates pollination, increases the number of fresh fruit bunches, eases harvesting, and prevents excessive evaporation during the dry season. The second technique is circle clearing, which involves clearing a circular area around the palm tree with a radius of 0.6–1.5 meters to prevent weed growth that could disrupt the plants. Pruning is categorized into three types based on the plant’s age: initial pruning, production pruning, and maintenance pruning. The number of fronds left on each tree ranges from 28 to 54. These care practices optimize plant growth, simplify farm management, and contribute to producing higher-quality palm oil yields.